A novel multi‐exon deletion in the dysferlin gene of a limb‐girdle muscular dystrophy type 2B Filipino patient. Issue 6 (7th October 2020) - Porto, Kristine Joyce L.; Mitsui, Jun; Ishiura, Hiroyuki; Kubota, Akatsuki; Luspian, Kathleen Jaye L.; Eduardo, Emmanuel; Damian, Ludwig; Toda, Tatsushi; Tsuji, Shoji
Abstract: We present a 34‐year‐old woman, from Philippines, diagnosed limb‐girdle muscular dystrophy type 2B with compound heterozygous nonsense mutation W1478* and novel deletion of exons 43‐46 of the dysferlin gene. These loss‐of‐function mutations do not seem to be predictive of a severer clinical course. We report the first identification of microhomologous region of 2 bp (TG) identical sequences surrounding the breakpoint junction. Detailed analysis of the deleted allele should be pursued in order to better understand the underlying mechanism of genomic rearrangements of the dysferlin gene.